Mental health, are we at risk? - Shabeena Tawar; Sanjana Seth Bhatia; Mookkiah Ilankumaran (Wolters Kluwer Medknow Publications, 2014)
Background: Mental health is an important component of the total positive health and is interwoven closely with the physical and physiological dynamics of the human body. Worldwide, about 500 million people are believed to be suffering from neurotic, stress related and psychological problems. In India, surveys on mental morbidity in various parts of the country suggest a prevalence rate of 18-20 per 1000. Materials and Methods: A community-based, cross-sectional descriptive study was carried out amongst married women in the age group 18-45 years in an urban community of South Mumbai. Self-reporting questionnaire of 20 items (SRQ 20) developed by the WHO was administered. Statistical analysis was carried out to estimate the prevalence of psychiatric disturbance. Result: The prevalence of psychiatric disturbance was found to be 27.27% for the total sample. The study results indicate that somatic symptoms were reported more commonly which could be a manifestation of underlying/burgeoning mental disorders. Conclusions: The results imply a high prevalence of 27.27% of psychiatric disturbance in our community. However, defining mental disorder from a clinical standpoint necessitates identification of the dividing line between despair and depression. It is recommended that women be encouraged to approach counsellors and thus enable further diagnosis and management of Common Mental Disorders in the community.